METODE PENYIMPANAN DAN PENGOLAHAN PANGAN HASIL TERNAK GUNA MENINGKATKAN KUALITAS KEAMANAN PANGAN (Universitas Wijayakusuma Purwokerto, 2024)
Food safety is recognized as a public health priority that requires a timely approach from production to consumption. In animal husbandry practices, guidelines are needed that aim to develop a quality assurance system for products originating from livestock, as well as addressing animal health, economic and environmental problems. To ensure food availability, many technologies for processing, handling and monitoring materials have been implemented. This food processing aims to maintain the quality of the food even though it is used for a long time. The counseling and discussion method is the method used in this service with the target of the activity being the Women of the Banyumas Regency Satpol PP Dharma Wanita Association. The result of the service activities is that partners understand better how to store and process livestock products, thereby increasing the innovation value of processed livestock products.